1982
DOI: 10.1007/bf00021654
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and quality characteristics of spring wheat lines selected for protein content and protein yield

Abstract: Triticum aestivum, wheat, protein percentage, protein yield, milling and baking data, recurrent selection. SUMMARYHigh protein cultivars of spring wheat (Triticum aestivum L.) from eight foreign countries and the United States were used in crosses to provide progeny for a recurrent selection program. After two cycles of selection, 40 lines selected for protein yield and 16 lines selected for protein percentage were evaluated with parents in yield nurseries at Bozeman, Montana.Lines selected for protein percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…Increasing of yield has been achieved by developing cultivars with poor protein content (Jenner et al 1991, Rharrabti et al 2001 because of negative correlation between yield and protein content (Bhatia 1975, McNeal et al 1982, O'Brien and Ronalds 1984, Peterson et al 1992, Liu et al 1995, Boggini et al 1997. In our research, negative correlation was confirmed to exist between yield and protein content.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increasing of yield has been achieved by developing cultivars with poor protein content (Jenner et al 1991, Rharrabti et al 2001 because of negative correlation between yield and protein content (Bhatia 1975, McNeal et al 1982, O'Brien and Ronalds 1984, Peterson et al 1992, Liu et al 1995, Boggini et al 1997. In our research, negative correlation was confirmed to exist between yield and protein content.…”
Section: Discussionsupporting
confidence: 65%
“…However, it is known that grain protein is negatively correlated with grain yield in wheat (Bhatia 1975, McNeal et al 1982, O'Brien and Ronalds 1984, Peterson et al 1992, Liu et al 1995, Boggini et al 1997, hence selection to increase one trait will tend to decrease the second trait (Jenner et al 1991, Rharrabti et al 2001. Despite this negative correlation, several studies have reported simultaneous improvement of grain yield and grain protein (Torp 1979, Cox et al 1985, Noaman et al 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Most agronomic characteristics were negatively correlated with protein; only main spike length, number of grains per plant, and number of effective spike were positively correlated, which corresponds well with the results of previous studies (McNeal et al, 1982;Holland et al, 2001;Khattak et al, 2005). We also found significant correlation between average grain weight per spike and quality characteristics at the level of 0.001.…”
Section: Hmw-gs Compositions From Triticum Aestivumsupporting
confidence: 92%
“…Lo¨ffler and Busch (1982) and Costa and Kronstad (1994) found that selection based on this approach would tend to increase yield and decrease protein concentration. McNeal et al (1982) obtained genotypes with high yield and intermediate protein concentration by selection for grain protein yield. However, where protein concentration per se is important, as in Canada, selection of lines with high deviation above the regression line of protein concentration on grain yield is probably a more effective way to increase both traits (Lo¨ffler and Busch 1982;Monaghan et al 2001).…”
mentioning
confidence: 99%